An S-Band Microstrip Patch Antenna Design and Simulation for Wireless Communication Systems - Md Sohel Rana; Sk Ikramul Islam; Sharif Al Mamun; Laltu Kumar Mondal; Md. Toukir Ahmed; Md. Mostafizur Rahman (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
In this paper, a 3.5 GHz microstrip patch antenna for the future of wireless communication is designed and studied. As a substrate, Rogers RT/Duroid5880 is utilized. This material has a thickness of 0.077mm and a dielectric loss of 2.2. The proposed antenna layout is simulated using the CST studio suite of software programs. This research aimed to achieve a lower return loss, higher gain, lower VSWR, directivity, and improved efficiency. The simulation revealed that the return loss, gain, VSWR, and directivity were correspondingly -13.772 dB, 7.55 dB, 1.5152, and 8.43dBi. The efficiency was 89.56%. This antenna has been developed and assessed for use in various wireless communication applications with a 3.5 GHz operating frequency, which is used as a reference antenna in communication satellites, weather radar, surface ship radar, wireless LAN-802.11b and 802.11g, multimedia applications in mobile TV and satellite radio, optical communications at 1460 to 1530 nm wavelength, and is utilized for other wireless fidelity applications.